Application of the C4.5 Algorithm for Identifying Regional Zone Status Using A Decision Tree in the Covid-19 Series - Rahardja, Untung (Aptisi Transactions On Technopreneurship (ATT), 2022)
Creativity is the act of coming up with an idea. In order to contribute to economic growth, entrepreneurs are currently adapting creativity in their business operations. Creativity is increasingly critical to business success in order to achieve the competitive edge in the aggressive business world. Thus, realizing the importance of this criterion, this study seeks to find out the level of creativity of science and technology (S&T) cluster students’ of University Technology Mara (UiTM) and how it affects them in terms of technopreneurship intention. The outcome of this study will illustrate whether S&T cluster students of UiTM have the creativity level in becoming the future technopreneurs and their ability to survive by adapting creativity and innovation at their workplace. It is found that creativity does impact one’s entrepreneurial intention and should be considered as part of the overall analysis in identifying one’s entrepreneurial competencies.